Pragmatics of the cinematographic experience - Capeller, Ivan (Estudos Semióticos, 2013)
We present a research about the relations between mimesis and the cinema that point out the insufficiency of notions such as “imitation” and “narrative” to describe the cinematographic experience and also make use of a non-representational ontology of the image that can be found in the deleuzian re-reading of Plato’s Allegory of the Cave, to demonstrate how, under any and all kinds of hermeneutics and/or iconologies, there is a latent kinematics of the mimesis that does not let itself be caught entirely by representational codes. The notion of simulacrum is articulated to Charles S. Peirce’s a-significant semiotics in order to think the cinematographic apparatus as a crucial factor in the understanding of the irreducibility of mimesis to its own self-generated forms of codified representation. The cinematographic mimesis is thus elaborated through a pragmatics of the cinematographic experience, as a kind of device that simultaneously and reciprocally modulates the objects of experience and the signs of representation in ways that are nor exclusively visual or even photographical, for all means of sensorial and conceptual expression are “mimetizable” by such a device. The cinematographic experience can be conceived of, at last, as a general mimetology of any and all experience, although organized according to its four noetic components: the generative, transformational, diagrammatical, and machinical components.